Algorithmic-Game Method Based on Algorithmic Thinking in Development Reflective Education Approach Place - Azamat o’g’li, Umarzoda Shahrukh (International Journal of Formal Education, 2025)
This in the article ALGORI-GAME hybrid education method algorithmic thinking in formation reflective approach with harmony analysis Research within Termez state university Practical mathematics 1st year students of the major in the presence of held experience based on method practical efficiency was evaluated . In the article reflection concept , its study in the activity types , in the ALGORI-GAME method reflective components and step by step formation theoretical and empirical basically open is given . Conclusion in part method improvement for modern technologies based on offers previously is pushed .